Cooperative Cluster Metalation and Ligand Migration in Zirconium Metal–Organic Frameworks. (23rd October 2015) - Yuan, Shuai; Chen, Ying‐Pin; Qin, Junsheng; Lu, Weigang; Wang, Xuan; Zhang, Qiang; Bosch, Mathieu; Liu, Tian‐Fu; Lian, Xizhen; Zhou, Hong‐Cai
Abstract: Cooperative cluster metalation and ligand migration were performed on a Zr‐MOF, leading to the isolation of unique bimetallic MOFs based on decanuclear Zr6 M4 (M=Ni, Co) clusters. The M 2+ reacts with the μ3 ‐OH and terminal H2 O ligands on an 8‐connected [Zr6 O4 (OH)8 (H2 O)4 ] cluster to form a bimetallic [Zr6 M4 O8 (OH)8 (H2 O)8 ] cluster. Along with the metalation of Zr6 cluster, ligand migration is observed in which a Zr–carboxylate bond dissociates to form a M–carboxylate bond. Single‐crystal to single‐crystal transformation is realized so that snapshots for cooperative cluster metalation and ligand migration processes are captured by successive single‐crystal X‐ray structures. In 3+ was metalated into the same Zr‐MOF which showed excellent catalytic activity in the acetaldehyde cyclotrimerization reaction. This work not only provides a powerful tool to functionalize Zr‐MOFs with other metals, but also structurally elucidates the formation mechanism of the resulting heterometallic MOFs. Abstract : Mischmetall‐MOF : Kooperative Clustermetallierung and Ligandverschiebung überführen ein Zr‐MOF in ein Zr6 M4 ‐basiertes Dimetall‐MOF (rechts). Auf diese Weise gelingt die Funktionalisierung von Zr‐MOFs mit anderen Metallen für verschiedene Anwendungen.